Can Spirituality Transform Our World? - King, Ursula (Journal for the Study of Spirituality, 2011)
In response to the wide-ranging question of the title, this article seeks to explore the profound impact that spiritualities have for personal and social transformation. I argue from a standpoint of a participatory hermeneutic that invites a personal engagement with the issues and choices of spirituality. First, I examine spirituality as a dynamic field, evident from the mutual interrelationship between spirituality and religion, as from the numerous debates about the meaning of spirituality. Second, I look at the topic in relation to the spiritual challenges of the contemporary world. These are enormous, and often very different from those of the past, yet they also point to a newly perceived global spiritual interdependence and a possible spiritual oneness of humanity. Spirituality is experienced in many new contexts, whether related to online activities, the public good or spiritual capital for society. The third section explores the idea of spiritualities for life, in relating spirituality to life's struggle, the need to effect change, and the transformative power of love. I conclude that spiritualities can offer a vision for hope and human flourishing; for the practical realization of this, more spiritual education for greater spiritual literacy and a widely needed global spiritual awakening are needed.